2016
DOI: 10.2214/ajr.15.14506
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Contrast-Enhanced Ultrasound Parameters in Crohn Disease: Their Role in Disease Activity Determination With Ultrasound

Abstract: Quantitative CEUS parameters integrated into inflammatory assessments with ultrasound reduce indeterminate results and improve disease activity level determinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 57 publications
5
53
0
Order By: Relevance
“…Recently, it was demonstrated that quantitative CEUS parameters integrated into inflammatory assessments by established grey-scale US with colour Doppler imaging reduce indeterminate results and improve CD activity level determinations [77].…”
Section: Ceusmentioning
confidence: 99%
“…Recently, it was demonstrated that quantitative CEUS parameters integrated into inflammatory assessments by established grey-scale US with colour Doppler imaging reduce indeterminate results and improve CD activity level determinations [77].…”
Section: Ceusmentioning
confidence: 99%
“…However there are increasing reports describing the utility of qualitative evaluation of bowel wall vascularity patterns in CD using CEUS [80, 81], as well as software defined quantitative metrics from time-intensity curves such as time-to-peak, peak enhancement and area under the curve [8285]. Promising data for evaluation of CD activity against an endoscopic reference have been reported [84, 86], as well as utility in stricture characterisation [87], detection of postoperative recurrence [88], and treatment response evaluation [89].…”
Section: Discussionmentioning
confidence: 99%
“…Promising data for evaluation of CD activity against an endoscopic reference have been reported [84, 86], as well as utility in stricture characterisation [87], detection of postoperative recurrence [88], and treatment response evaluation [89]. Apparent diagnostic benefit over conventional US parameters is also described [85] .…”
Section: Discussionmentioning
confidence: 99%
“… It has been found that disease activity correlates with increased vascularity . Color Doppler imaging is an important technique that has traditionally been used to detect vascular signals from blood vessels in the bowel wall as a qualitative measure of active inflammation . Bowel intramural angiogenesis and inflammation have also been well shown on CT and MRI and confirmed by histologic analysis .…”
Section: Bowel With Ibdmentioning
confidence: 99%
“…The grading of the classic grayscale parameters of bowel wall thickness, color Doppler signal, and perienteric inflammatory fat allows us to generate an overall assessment of disease activity using a USGA (Table ) . Lymphadenopathy is not included in the USGA.…”
Section: Overall Bowel Disease Grading: Usgamentioning
confidence: 99%